Oxygen-evolving electrode

CN116209788BActive Publication Date: 2026-10-27DE NORA PERMELEC LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180060729.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-07-20
Filing Date
2021-05-26
Publication Date
2026-10-27
Estimated Expiration
2041-05-26

AI Technical Summary

Technical Problem

然而,由于铱是最昂贵且稀有的元素之一,因此,作为用于构成电解采集工艺用阳极的催化剂层的材料,在经济性方面存在缺乏通用性的课题

Benefits of technology

[0029]根据本发明,可以提供一种具备电导率高、且即使在电解酸性电解液的情况下催化剂成分也不易被消耗、能长时间电解的耐久性优异的催化剂层的产氧用电极。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116209788B_ABST
    Figure CN116209788B_ABST
Patent Text Reader

Abstract

Provided is an oxygen-producing electrode having a catalyst layer with high electrical conductivity, in which the catalyst component is not easily consumed even when an electrolytic acid electrolyte is used, and the electrode can be electrolyzed for a long time. An oxygen-producing electrode (10) includes a substrate (2) formed of titanium or a titanium alloy, and a catalyst layer (4) formed of a mixed metal oxide and disposed on the substrate (2), the catalyst layer (4) satisfying at least any one of the following conditions (1) and (2). Condition (1): contains ruthenium, tin, and a multivalent metal element having a valence of 3 or more (excluding 4). Condition (2): contains ruthenium and tin, and the content of ruthenium is 40 mol% or more based on the total content of ruthenium and tin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electrode for oxygen production. Background Technology

[0002] In the electrolytic extraction process of non-ferrous metals such as copper, nickel, and zinc, sulfuric acid or strongly acidic electrolytes are typically used. Furthermore, the anode, which serves as the counter electrode, can be an oxygen-generating electrode that initiates the oxygen-generating reaction. A titanium electrode, with a coating layer containing mixed metal oxides (MMO) as a catalyst layer on its surface, has been proposed as an anode for electrolytic extraction processes that reduces energy consumption due to its lower overvoltage characteristics for the oxygen-generating reaction, replacing the lead alloy electrode conventionally used for oxygen generation.

[0003] The mixed metal oxides used to form the catalyst layer are typically composite oxides of iridium (Ir) as the active element and valve metals such as tantalum (Ta), tin (Sn), titanium (Ti), zirconium (Zr), and niobium (Nb) as binder elements. As an electrode using such a composite oxide, a titanium electrode for oxygen generation with a catalyst layer containing IrO2-Ta2O5 has been proposed (Non-Patent Document 1). However, since iridium is one of the most expensive and rarest elements, it lacks versatility in terms of economics as a material for the catalyst layer used to construct the anode in electrolytic harvesting processes.

[0004] In contrast, ruthenium (Ru) oxide (RuO2), which is known to be cheaper than iridium, has shown high electrode catalytic activity for the oxygen evolution reaction (OER) and has attracted much attention as an alternative to iridium. For example, a titanium electrode with a catalyst layer containing RuO2-Ta2O5 as a composite oxide that does not use iridium has been proposed (Non-Patent Document 2).

[0005] Existing technical documents

[0006] Non-patent literature

[0007] Non-patent literature 1: Journal of Applied Electrochemistry, 1991, 21, pp. 335-345; Non-patent literature 2: Proceedings of Copper 2016 (Abstract Collection), pp. 2145-2152. Summary of the Invention

[0008] The problem the invention aims to solve

[0009] However, if ruthenium is used as the active element in the catalyst layer of the titanium electrode used for oxygen generation, there is a problem of reduced catalyst layer durability. Therefore, oxygen generation electrodes with catalyst layers containing ruthenium as the active element are, for example, difficult to apply to long-term electrolysis lasting for many years.

[0010] The present invention was made in view of the problems of the prior art, and its objective is to provide an electrode for oxygen generation with a catalyst layer having excellent durability, high conductivity, and the catalyst components are not easily consumed even when electrolyzing acidic electrolytes, and can be electrolyzed for a long time.

[0011] Solution for solving the problem

[0012] That is, according to the present invention, an oxygen-generating electrode as shown below is provided.

[0013] [1] An electrode for oxygen generation, comprising:

[0014] Substrates made of titanium or titanium alloys, and

[0015] A catalyst layer formed of mixed metal oxides and disposed on the aforementioned substrate,

[0016] The aforementioned catalyst layer satisfies at least any one of the following conditions (1) and (2).

[0017] Condition (1): Contains ruthenium, tin and polyvalent metal elements with a valence of 3 or higher (excluding those with a valence of 4).

[0018] Condition (2): Contains ruthenium and tin, and the total content of ruthenium and tin is used as the benchmark, with the ruthenium content being 40 mol% or more.

[0019] [2] According to the oxygen-generating electrode described in [1] above, wherein the catalyst layer satisfies the aforementioned condition (1),

[0020] Using all the metal elements in the aforementioned catalyst layer as a benchmark, the content of the aforementioned multivalent metal elements in the aforementioned catalyst layer is 2 to 20 moles.

[0021] [3] According to the oxygen-generating electrode described in [1] or [2] above, the aforementioned multivalent metal element is at least one selected from the group consisting of bismuth, tantalum, lanthanum, niobium and molybdenum.

[0022] [4] The oxygen-generating electrode according to any one of [1] to [3] above, wherein the catalyst layer satisfies the aforementioned condition (1),

[0023] Using all the metal elements in the aforementioned catalyst layer as a benchmark, the ruthenium content in the aforementioned catalyst layer is 20–70 mol%.

[0024] [5] The oxygen-generating electrode according to any one of [1] to [4] above, wherein the catalyst layer further contains manganese.

[0025] [6] The oxygen-generating electrode according to any one of [1] to [5] above further comprises an intermediate layer disposed between the aforementioned substrate and the aforementioned catalyst layer.

[0026] [7] The oxygen-generating electrode according to any one of [1] to [6] above, wherein it further comprises a barrier layer disposed on the aforementioned catalyst layer.

[0027] [8] The oxygen-generating electrode according to any one of [1] to [7] above is used as an anode in the electrolytic collection process of non-ferrous metals.

[0028] The effects of the invention

[0029] According to the present invention, an electrode for oxygen generation with a catalyst layer having high conductivity, and excellent durability that is not easily consumed even when electrolyzing acidic electrolytes, and can be electrolyzed for a long time can be provided. Attached Figure Description

[0030] Figure 1 This is a schematic diagram illustrating one embodiment of the oxygen-generating electrode of the present invention.

[0031] Figure 2 This is a schematic diagram illustrating another embodiment of the oxygen-generating electrode of the present invention.

[0032] Figure 3 This is a schematic diagram illustrating another further embodiment of the oxygen-generating electrode of the present invention.

[0033] Figure 4 This is a schematic diagram illustrating another further embodiment of the oxygen-generating electrode of the present invention. Detailed Implementation

[0034] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments. The oxygen-generating electrode of the present invention comprises: a substrate formed of titanium or a titanium alloy, and a catalyst layer disposed on the substrate and formed of a mixed metal oxide. Moreover, the catalyst layer satisfies at least any one of the following conditions (1) and (2). Hereinafter, the details of the oxygen-generating electrode of the present invention will be described.

[0035] Condition (1): Contains ruthenium, tin and polyvalent metal elements with a valence of 3 or higher (excluding those with a valence of 4).

[0036] Condition (2): Contains ruthenium and tin, and the total content of ruthenium and tin is used as the benchmark, with the ruthenium content being 40 mol% or more.

[0037] (Substrate)

[0038] Figure 1 This is a schematic diagram illustrating one embodiment of the oxygen-generating electrode of the present invention. Figure 1 As shown, the oxygen-generating electrode 10 of this embodiment includes a substrate 2 and a catalyst layer 4 disposed on the substrate 2. The substrate 2 is formed of titanium or a titanium alloy. The overall shape of the substrate 2 is not particularly limited and can be appropriately designed according to the application. Examples of the overall shape of the substrate include a plate shape, a rod (column) shape, and a mesh shape.

[0039] (Catalyst layer)

[0040] The catalyst layer 4 disposed on the substrate 2 is formed of a mixed metal oxide. Figure 1 The mixed metal oxide is a composite oxide of multiple metal elements and functions as a catalyst for electrolysis. Moreover, the catalyst layer is a layer that satisfies at least any one of the following conditions (1) and (2), and preferably a layer that satisfies both conditions (1) and (2).

[0041] Condition (1): Contains ruthenium, tin and polyvalent metal elements with a valence of 3 or higher (excluding those with a valence of 4).

[0042] Condition (2): Contains ruthenium and tin, and the total content of ruthenium and tin is used as the benchmark, with the ruthenium content being 40 mol% or more.

[0043] There is no particular limitation on the thickness of the catalyst layer; it can be set arbitrarily. For example, the thickness of the catalyst layer can be set to 1–10 μm.

[0044] [Condition (1)]

[0045] The catalyst layer contains ruthenium (Ru), tin (Sn), and polyvalent metal elements with a valence of 3 or higher (excluding those with a valence of 4) (hereinafter also referred to as "polyvalent metal elements"). That is, the catalyst layer is formed by a composite oxide, i.e., a mixed metal oxide, of ruthenium as the active element, tin as the binder element, and the aforementioned polyvalent metal elements. In addition to ruthenium and tin, which are tetravalent metal elements, polyvalent metal elements with valences different from these tetravalent metal elements can coexist in the catalyst layer, thereby increasing the conductivity and forming an electrode for oxygen production with a lower electrode potential. Furthermore, by containing polyvalent metal elements, the catalyst components (especially ruthenium as the active element) are less likely to be consumed under acidic conditions such as sulfuric acid, resulting in a catalyst layer with excellent durability. It should be noted that the valence of metal elements in this specification refers to the valence (oxidation number) of the metal element that exists in its most stable state.

[0046] Examples of multivalent metal elements include bismuth (Bi), tantalum (Ta), lanthanum (La), niobium (Nb), and molybdenum (Mo). Among these, bismuth, tantalum, lanthanum, and niobium are preferred, with bismuth being even more preferred. These multivalent metal elements can be used alone or in combination of two or more.

[0047] When the catalyst layer meets condition (1), taking all metal elements in the catalyst layer as a reference, the content of polyvalent metal elements in the catalyst layer is preferably 2 to 20 mol%, more preferably 3.5 to 15 mol%, and particularly preferably 4 to 12 mol%. By making the content of polyvalent metal elements in the catalyst layer within the above range, the conductivity can be further improved, and the durability of the catalyst layer can be further improved. It should be noted that if the content of polyvalent metal elements in the catalyst layer is too low, the effect obtained by containing polyvalent metal elements may sometimes be slightly insufficient. On the other hand, if the content of polyvalent metal elements in the catalyst layer is too high, the content of ruthenium as an active element and tin as a binder element will be relatively reduced, and therefore, the catalytic activity may sometimes be slightly insufficient. It should be noted that the types and contents of metal elements in each layer containing the catalyst layer can be determined and calculated by analytical methods such as X-ray fluorescence (XRF) analysis.

[0048] When the catalyst layer meets condition (1), taking all metal elements in the catalyst layer as a reference, the ruthenium content in the catalyst layer is preferably 20-70 mol%, more preferably 25-66 mol%, and particularly preferably 30-55 mol%. By keeping the ruthenium content in the catalyst layer within the above range, higher catalytic activity can be obtained. It should be noted that if the ruthenium content in the catalyst layer is too low, the catalytic activity may be slightly insufficient. On the other hand, if the ruthenium content in the catalyst layer is too high, it becomes easier for the ruthenium component to aggregate. In addition, for the coating amount, the proportion of ruthenium, which does not effectively contribute to the electrolysis reaction, becomes higher, and the proportion of binder component becomes lower, thereby sometimes reducing durability.

[0049] [Condition (2)]

[0050] The catalyst layer contains ruthenium (Ru) and tin (Sn), with the total content of ruthenium and tin as a benchmark, the ruthenium content is 40 mol% or more. That is, the catalyst layer is formed from a composite oxide, i.e., a mixed metal oxide, of ruthenium as the active element and tin as the binder element. It should be noted that the catalyst layer is preferably formed from a composite oxide, i.e., a mixed metal oxide, that substantially contains only ruthenium and tin as metal elements. Furthermore, by setting the ruthenium content to 40 mol% or more, preferably 43 mol% or more, and even more preferably 45 mol% or more, based on the total content of ruthenium and tin, the conductivity can be improved, and an electrode for oxygen generation with a lower electrode potential can be formed. Moreover, by setting the ruthenium content within the above range, the catalyst components (especially ruthenium as the active element) are not easily consumed even under acidic conditions such as sulfuric acid electrolysis, resulting in a catalyst layer with excellent durability.

[0051] [Other metallic elements]

[0052] The catalyst layer may also contain metallic elements other than ruthenium and tin (other metallic elements). By including other metallic elements in the catalyst layer, they can function as quasi-active components for the electrolysis reaction. Examples of such other metallic elements include manganese (Mn). That is, the catalyst layer preferably also contains manganese.

[0053] When other metal elements are contained in the catalyst layer, all metal elements in the catalyst layer are used as a reference, and the content of other metal elements in the catalyst layer is usually 10 to 50 mol%, preferably 20 to 40 mol%.

[0054] (Middle layer)

[0055] Figure 2 This is a schematic diagram illustrating another embodiment of the oxygen-generating electrode of the present invention. Figure 2 The oxygen-generating electrode 20 shown also includes an intermediate layer 6 disposed between the substrate 2 and the catalyst layer 4. By providing this intermediate layer between the substrate and the catalyst layer, passivation of the titanium or titanium alloy substrate caused by electrolysis can be suppressed, and the substrate can be kept free from corrosion, which is therefore preferable. As a result, durability can be further improved, forming an oxygen-generating electrode capable of undergoing longer-term electrolysis.

[0056] The interlayer can be formed from various metals. Examples of metals used to form the interlayer include titanium (Ti), tantalum (Ta), tin (Sn), their alloys, and mixed oxides thereof. Among these, alloys of titanium and tantalum, and mixed oxides of titanium and tantalum are preferred. The thickness of the interlayer is not particularly limited and can be set arbitrarily. For example, a thickness of 0.2–5 μm is sufficient.

[0057] (Barrier layer)

[0058] Figure 3 and 4 This is a schematic diagram illustrating another further embodiment of the oxygen-generating electrode of the present invention. Figure 3 The oxygen-generating electrode 30 shown includes a substrate 2, a catalyst layer 4 disposed on the substrate 2, and a barrier layer 8 disposed on the catalyst layer 4. Additionally, Figure 4 The oxygen-generating electrode 40 shown includes a substrate 2, a catalyst layer 4 disposed on the substrate 2, and further includes an intermediate layer 6 disposed between the substrate 2 and the catalyst layer 4, and a barrier layer 8 disposed on the catalyst layer 4. That is, Figure 3 and 4Both the oxygen-generating electrodes 30 and 40 shown further include a barrier layer 8 disposed on the catalyst layer 4. By providing this barrier layer (surface coating) on ​​the catalyst layer, the consumption of components such as ruthenium in the catalyst layer can be reduced, which is therefore preferable. Furthermore, it can suppress the diffusion of components such as arsenic (As), antimony (Sb), and manganese (Mn) present in the electrolyte and potentially deposited through electrolysis to the surface of the catalyst layer. As a result, durability can be further improved, forming an oxygen-generating electrode capable of longer-term electrolysis.

[0059] The barrier layer can be formed, for example, from a mixed metal oxide, i.e., a composite oxide of multiple metal elements, similar to the mixed metal oxide used to form the catalyst layer. Besides ruthenium and tin, the barrier layer can also be formed from a composite oxide of the aforementioned multivalent metal elements, i.e., a mixed metal oxide. Using all metal elements in the barrier layer as a reference, the content of active metal elements such as ruthenium in the barrier layer is preferably 0.5% to 5%. Furthermore, using all metal elements in the barrier layer as a reference, the content of binder elements such as tin in the barrier layer is preferably 95% to 99.5 mol%.

[0060] There is no particular limitation on the thickness of the barrier layer; it can be set arbitrarily. For example, the thickness of the barrier layer can be set to 0.5–5 μm.

[0061] (Applications of electrodes for oxygen production)

[0062] The oxygen-generating electrode of the present invention has high conductivity, and even in acidic electrolytes such as sulfuric acid, the ruthenium in the catalyst layer is not easily consumed, exhibiting durability suitable for long-term electrolysis. Therefore, the oxygen-generating electrode of the present invention is useful, for example, as an anode (electrolytic anode) for non-ferrous metal electrolytic collection processes, used in combination with a cathode (cathode) for non-ferrous metal electrolytic collection. Furthermore, it is suitable for applying a current density of 10 A / m. 2 The following electrodes for oxygen production in electrolysis processes are useful.

[0063] (Manufacturing method of electrode for oxygen generation)

[0064] The oxygen-generating electrode of the present invention can be manufactured by forming a catalyst layer of mixed metal oxides on a substrate. To form the catalyst layer on the substrate, a coating liquid containing, for example, various metals and salts of various metals in a desired ratio is prepared, and the prepared coating liquid is applied to the surface of a substrate that has undergone surface treatments such as spraying or etching, thereby forming a coating layer. Next, firing is performed under appropriate temperature conditions to form the catalyst layer of mixed metal oxides on the substrate, thus obtaining the target oxygen-generating electrode. It should be noted that by repeatedly applying the coating liquid and firing, the thickness of the formed catalyst layer and the content of metal elements can be controlled. The firing temperature is typically set to 450–550°C, preferably 480–520°C.

[0065] Before forming the catalyst layer, an intermediate layer can also be formed on the substrate. To form the intermediate layer on the substrate, similar to the process for forming the catalyst layer described above, a coating solution containing various metals and metal salts in a desired ratio is first applied to the surface of the substrate to form a coating layer. Next, firing is performed under appropriate temperature conditions, thereby forming the intermediate layer on the substrate. By repeating the application of the coating solution and firing, the thickness and metal element content of the formed intermediate layer can be controlled. The firing temperature is typically set to 450–550°C, preferably 480–520°C. On the formed intermediate layer, a catalyst layer can be formed according to the aforementioned steps.

[0066] Alternatively, the intermediate layer can also be formed on the substrate by ion plating, sputtering, plasma spraying, or other methods.

[0067] To form a barrier layer on the catalyst layer, similar to the process described above, a coating solution containing various metals and metal salts is first applied to the surface of the catalyst layer to form a coating layer. Next, firing is performed under appropriate temperature conditions to form a barrier layer on the catalyst layer. By repeating the application of the coating solution and firing, the thickness of the formed barrier layer and the content of the metal elements can be controlled. The firing temperature is typically 450–550°C, preferably 480–520°C.

[0068] Example

[0069] The present invention will now be described in detail based on embodiments, but the present invention is not limited to these embodiments. It should be noted that, unless otherwise specified, "parts" and "%" in the embodiments and comparative examples refer to quality standards.

[0070] <Substrate Pretreatment>

[0071] Prepare a 100mm × 100mm × 1mm titanium mesh substrate. Anneal the substrate in air at 590°C for 60 minutes, then perform alumina (#60) blasting. Immerse it in boiling 20% ​​hydrochloric acid for 12 minutes for etching, then rinse with deionized water and dry to obtain the pretreated substrate.

[0072] <Formation of the intermediate layer>

[0073] (Method (A))

[0074] A pretreated substrate was mounted on an arc ion plating apparatus using a Ta-Ti alloy target as the evaporation source. Then, an intermediate layer of Ta-Ti alloy was formed on the surface of the substrate according to the coverage conditions shown in Table 1.

[0075] [Table 1]

[0076]

[0077] (Method (B))

[0078] A coating solution with a Ti:Ta ratio of 50:50 was prepared by mixing 270 g / L TiCl4 solution, 125 g / L TaCl5 solution, and 10% hydrochloric acid aqueous solution. The prepared coating solution was brushed onto the surface of a pretreated substrate and dried at 60 °C for 10 minutes. The substrate was then calcined in an electric muffle furnace at 520 °C for 10 minutes in air atmosphere, followed by air cooling to room temperature. This cycle of coating solution application and air cooling was repeated until the coating weight reached 1.3 g / m². 2 (Metal mass conversion) An intermediate layer of mixed oxides of Ta-Ti is formed on the surface of the substrate.

[0079] <Manufacturing of electrodes for oxygen generation>

[0080] (Example 1)

[0081] [Formation of the catalyst layer]

[0082] A 1.65 mol / L solution of tin (Sn) hydroxyacetyl chloride complex (SnHAC) was prepared according to the steps described in International Publication No. 2005 / 014885. A 0.9 mol / L solution of ruthenium (Ru) hydroxyacetyl chloride complex (RuHAC) was prepared according to the steps described in International Publication No. 2010 / 055065. An 80 g / L Bi solution was prepared by dissolving BiCl3 in a 10% aqueous hydrochloric acid solution. A 130 g / L Mn solution was prepared by dissolving Mn(NO3)2·6H2O in a 10% aqueous acetic acid solution. The RuHAC solution, Mn solution, SnHAC solution, Bi solution, and 10% aqueous acetic acid solution were mixed to prepare a coating solution with a molar ratio of Ru:Mn:Sn:Bi = 33:20:43:4. After brushing the prepared coating liquid onto the intermediate layer of a substrate on which an intermediate layer has been formed by the aforementioned method (A), the substrate is dried at 60°C for 10 minutes. Then, it is fired in an electric muffle furnace at 520°C for 10 minutes in an air atmosphere, followed by air cooling to room temperature. This cycle of coating liquid application and air cooling is repeated until the coating weight reaches 10 g / m². 2 (Mass conversion of Ru and Mn), a catalyst layer is formed on the intermediate layer.

[0083] [Formation of the barrier layer]

[0084] A coating solution with a Sn:Bi:Ru ratio of 95:2:3 was prepared by mixing RuHAC solution, SnHAC solution, Bi solution, and 10% aqueous acetic acid solution. The prepared coating solution was brushed onto the catalyst layer and dried at 60°C for 10 minutes. After calcination at 520°C for 10 minutes in an electric muffle furnace under air atmosphere, the layer was air-cooled to room temperature. This cycle of coating solution application and air cooling was repeated until the coating weight reached 3 g / m³. 2 (Sn mass conversion), a barrier layer is formed on the catalyst layer to obtain an electrode for oxygen production.

[0085] (Examples 2-11, Comparative Examples 1-3)

[0086] Each material was used in the manner shown in Table 2 to form the layer structure, and firing was performed under the conditions shown in Table 2. Otherwise, the oxygen-generating electrode was manufactured in the same manner as in Example 1 described above. It should be noted that after forming the catalyst layer, post-baking was performed in an electric muffle furnace under an air atmosphere at 520°C for 1 hour. Furthermore, the tantalum (Ta), lanthanum (La), niobium (Nb), and iridium (Ir) sources used in the coating solution for forming the catalyst layer were those shown below.

[0087] • Tantalum (Ta) source: 125 g / L TaCl5 solution

[0088] ·Lanthanum (La) source: La(NO3)3·6H2O

[0089] ·Niobium (Nb) source: ammonium niobium(V) oxalate hydrate

[0090] ·Iridium (Ir) source: 20.5% chloroiridic acid solution

[0091] [Table 2]

[0092] Table 2

[0093]

[0094] <Evaluation>

[0095] (Measurement of Electrode Potential)

[0096] The electrode potential (V) of the manufactured oxygen-generating electrode under oxygen generation conditions was measured according to the method shown below. The results are shown in Table 3.

[0097] ·Current interruption method

[0098] ·Electrolyte: 150 g / L sulfuric acid aqueous solution

[0099] ·Electrolyte temperature: 50°C

[0100] ·Working electrode area: 10 mm × 10 mm

[0101] ·Counter electrode: Zr plate (20 mm × 70 mm)

[0102] ·Reference electrode: mercurous sulfate (Hg / Hg2SO4)

[0103] [Table 3]

[0104] Table 3

[0105]

[0106] (Durability Test)

[0107] A durability test of the oxygen-generating electrode (catalyst layer) was performed according to the conditions shown below.

[0108] ·Electrolyte: 150 g / L sulfuric acid aqueous solution

[0109] ·Electrolyte temperature: 40°C

[0110] ·Anode area: 20 mm × 50 mm

[0111] ·Cathode: Zr plate (30 mm × 70 mm)

[0112] ·Current density applied to the anode: 300 A / m 2

[0113] The coating residue after a constant time was determined by XRF analysis, and the consumption of active metal elements (Ru, Mn, Ir) was calculated. g / m 2 In addition, the consumption rate (m) of the active metal elements (Ru, Mn, Ir) is calculated from the calculated consumption and electrolysis time. g / m 2 / hour). The results are shown in Table 4.

[0114] [Table 4]

[0115] Table 4

[0116]

[0117] Industrial availability

[0118] The oxygen-generating electrode of the present invention can be used as an anode in the electrolytic collection process of non-ferrous metals, or as an electrode for applying a current density of 10 A / m. 2 The oxygen-generating electrodes used in the following electrolysis process are useful.

[0119] Explanation of reference numerals in the attached figures

[0120] 10, 20, 30, 40: Electrodes for oxygen production

[0121] 2: Substrate

[0122] 4: Catalyst layer

[0123] 6: Intermediate layer

[0124] 8: Barrier layer

Claims

1. An electrode for oxygen generation, comprising: Substrates made of titanium or titanium alloys, and A catalyst layer formed of mixed metal oxides and disposed on the substrate, The catalyst layer satisfies the following condition (1). Condition (1): Contains ruthenium, tin, and a polyvalent metal element with a valence of 3 or higher, excluding polyvalent metal elements with a valence of 4. The polyvalent metal element is bismuth. Using all the metal elements in the catalyst layer as a reference, the content of the multivalent metal elements in the catalyst layer is 4~12 moles.

2. The electrode for oxygen generation according to claim 1, wherein, The catalyst layer satisfies condition (1). Using all the metal elements in the catalyst layer as a reference, the ruthenium content in the catalyst layer is 20~70 moles.

3. The oxygen-generating electrode according to claim 1 or 2, wherein, The catalyst layer also contains manganese.

4. The oxygen-generating electrode according to claim 1 or 2, wherein, It also includes an intermediate layer disposed between the substrate and the catalyst layer.

5. The oxygen-generating electrode according to claim 1 or 2, wherein, It also has a barrier layer disposed on the catalyst layer.

6. The oxygen-generating electrode according to claim 1 or 2, which is used as an anode in the electrolytic collection process of non-ferrous metals.

Citation Information

Patent Citations

  • Electrode for electrolysis cell

    WO2010055065A1

  • Catalytic coating and method of manufacturing thereof

    CN106471159A

  • Electrode for electrolytic processes

    US20180127887A1

  • Electrode and method of preparing same

    US4530742A